NGO-led activism under authoritarian rule of Vietnam: Between cooperation and contestation. Issue 4 (8th August 2019) - Vu, Anh Ngoc
ABSTRACT: There is a significant lacuna in the literature on civil society activism in authoritarian contexts. This research addresses this gap by providing an innovative conceptual framework that draws upon relational approach to civil society and mainstream social movement theories. The research focuses on legitimacy, autonomy as well as formality and informality as defining characteristics of civil society activism. In the light of this framework, the paper provides an in-depth empirical account of the processes through which a local NGO in one-party ruled Vietnam orchestrates community mobilization to improve policy delivery response to the poor. This paper argues that by taking advantage of their embedded relation into the state, working within and through bureaucratic structures, manipulating available structural links, as well as strategizing around both formal and informal channels of activism, Vietnamese NGOs are seeking to carve out more room for themselves to manoeuvre in critical actions.